PENGARUH PEMBERIAN Zn TERHADAP KADAR GLUKOSA DARAH DAN KADAR SUPEROKSIDA DISMUTASE PADA TIKUS WISTAR YANG DIINDUKSI STREPTOZOTOCIN - Kartika, Nadini; Rachmawati, Banundari; Johan, Andrew (Jurnal Kesehatan, 2016)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Giving Zn could reduce the reactivity of ROS due to hyperglycemia by increasing SOD status. Zinc ability as an antioxidant also can improve blood glucose level in diabetes mellitus patients. To prove the effect of Zn with the doses of 3 mg/kg BW and 5 mg/kg BW for 30 days onblood glucose and SOD levels in Wistar rats induced by STZ. Twenty-eight rats were divided into 4 groups includes K1 as a negative control group, K2 as a positive control group that is induced by STZ 40 mg/kg BW, K3 as? group that is induced by STZ 40 mg/kg BW and Zn were given at a dose of 3 mg/kg BW for 30 days orally and K4 as aa group that is induced by STZ 40 mg/kg BW and Zn were given at a dose of 5 mg/kg BW for 30 days orally. Examination of blood glucose levels used GODPAP methods and SOD levels checked with a colorimeter method. Data were analyzed using Paired T-Testsand Wilcoxon tests. There was a significant decrease in blood glucose levels after administration of 3 mg/kg BW Zn (p = 0,003) and 5 mg/kg BW (p = 0.018) for 30 days in Wistar rats induced by STZ. There was no significant increase in SOD levels after administration of 3 mg/kg BW Zn (p = 0,120) but a significant increase in SOD levels after administration of 5 mg/kg BW Zn (p = 0,038) for 30 days in Wistar rats induced by STZ. Administration of 5 mg/kg BW Zn for 30 days showed a better effect on blood glucose and SOD levels in Wistar rats induced by STZ when compared with administration of 3 mg/kg BW Zn.